Gallstone Ileus with Atypical Clinical Presentation: A Case Report - Flores-López, Alejandro Alberto; Espinosa-Rosales, Alicia Valeria; Falcón-Cancino, Luis Arturo; Carrillo-Pinto, Laura Daniela Caridad; Gómez-Salazar, Adriana Guadalupe; Santana-Valencia, Juan Ignacio; Quijano-Soberanis, Vanessa Alejandra; Villalobos-Rodríguez, Alejandro Lenin; Padrón-Arredondo, Guillermo (British Journal of Healthcare and Medical Research, 2023)
Introduction: Gallstone ileus is a rare complication of cholelithiasis, described as a mechanical intestinal obstruction due to the impaction of one or more large gallstones within the gastrointestinal tract. It is caused by the passage of a gallstone from the bile ducts into the intestinal lumen through a fistula. The most frequent type of fistula is located between the gallbladder and the duodenum. Clinical Case: A 60-year-old male was admitted with a diagnosis of DM 2 / hypovolemic shock / upper gastrointestinal bleeding. Began 24 h before admission, presented asthenia, adynamia, hyporexia, tolerating only a liquid diet, 3 vomits of gastric contents and one melenic evacuation. level of care for surveillance and diagnostic protocol, upon admission to this hospital he presented vomiting in coffee grounds and hypotension that responded to intravenous fluids. An exploratory laparotomy was performed, finding: obstruction of the small intestine by a gallstone of approximately 7 cm in diameter at 170 cm from the angle of Treitz, reactive appendicitis, and abundant inflammatory reaction fluid; Enterolithotomy + primary closure was performed with the Heineke-Mikulikcz technique and a Penrose drain was placed into the pelvic cavity. Discussion: Intestinal obstruction caused by gallstones is rare, this event occurs more frequently in the elderly. The clinical picture is often diffuse and requires a high index of suspicion. Conventional radiography can be of great help for its diagnosis, but also Abdominal Ultrasound and Computerized Axial Tomography. Surgical treatment can range from enterotomy and lithotomy, which is the simplest, to enterotomy with lithotomy plus cholecystectomy, and fistula treatment, which is a complex procedure.